Correction: Bustamante et al. Determining When an Algebra Is an Evolution Algebra. Mathematics 2020, 8, 1349 - Miguel D. Bustamante; Pauline Mellon; M. Victoria Velasco (Mathematics, 2021)
The authors wish to make the following corrections to this paper [1] (see corrected version in postprint [2]):On page 2, paragraph 4, complete the first sentence ‘In Theorem 2 we show that if A is a real algebra and B is a basis of A then B also is a basis of <semantics>Aℂ</semantics>, the complexification of A (with the same multiplication structure matrices) and that A is an evolution algebra if, and only if, <semantics>Aℂ</semantics> is an evolution algebra’ with the phrase ‘and has a natural basis consisting of elements of A’ [...]